Development of System Dynamic Models for Improving E-Governments Performance Local Governments in Lampung Province - Ida Nurhaida; Andi Windah; Nina Yudha Aryanti; Arif Sugiono (Journal of Governance, 2023)
Abstract:  The development of communication and information technology requires the adaptation of all elements of society, including Government of Indonesia. Referring to the various dynamics of e-government problems, it is deemed necessary to develop dynamic system model to improve the e-government performance of local governments, especially in Lampung Province. The research is aimed at developing a model that can be simulated for improving e-Government performance by measuring the qualitative contribution of each component, both the ICT component and the social component that will be produced in this study, which can be useful for every local government in Lampung Province in accelerating and developing e -government. The research’s model is done using VENSIM application for modeling and simulating complex systems in a variety of variables to improve the local government performance. This research finds that there are five main variables that constructed the improvement of e-government of local government performance: (1) e-government policies, HR, infrastructure, and management; (2) service, (3) performance, (4) community/user, and (5) quality of community life. The dynamic model can be further seen in the appendix.